Rancang Bangun dan Uji Kelayakan Finansial Alat Pengering Mekanis untuk Pemenuhan Pasokan Eceng Gondok (Eichhornia Crassipes) sebagai Bahan Baku Kerajinan - Kunto Purbono; Makhmudun Ainuri; Suryandono Suryandono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2010)
Mechanical dryer is needed to accomplishment of dry eichhornia crassipes materials and quality increasing of materi- als and eichhornia crassipes handicraft products. The research method used to design of mechanical dryer and feasi- bility test of technical, quality of materials result of draining, and finance. The result of the research was mechanical dryer of ‘cabinet dryer’ type which has dimension of length x width x height 120 x 120 x 208 (cm3), maximal capacity80 (kg/10hours) with wood coal fire source, and drying duration for 10 hours. The average highest of temperature per-formance was reached at chimney drying 50 (kg/10hours) capacity was 62,3 0C, with temperature distribution between62,95 0C-65,45 0C, the highest heat requirement was reached by chimney dryer 80 (kg) capacity was 14.087,1 (kJ) with 36,753 % efficiency, 12,195 % moisture content, and 16,26397 (kg/hour) was needed for drying air. The maximum average of tensile strength was reached by chimney drying 50 (kg) capacity was 23,537 (N/mm2), while the maximum tensile strength in sun drying as 15,681 (N/mm2), eichhornia crassipes’s color most coming near to natural colour (green’s colour) at chimney drying was L 36, while the colour in sun drying at L 51, 89. Financially, with the analysis of incremental BCR was 1,015, analysis of NPV Rp. 2.569.148,31, IRR 39 %, BEP was reached after the drier has been producing 962,1 (kg)(s) or equivalent to cost Rp.5.291.288,30, so that mechanical dryer usage for drying of eichhornia crassipes can get good benefit.ABSTRAKAlat pengering mekanis diperlukan guna pemenuhan pasokan bahan baku eceng gondok kering dan peningkatan kuali- tas bahan dan produk kerajinan eceng gondok. Metode penelitian yang digunakan yaitu rancang bangun dan uji ke- layakan teknis, kualitas bahan hasil pengeringan, dan finansial. Hasil penelitian, alat pengering mekanis tipe cabinet dryer, dengan dimensi panjang x lebar x tinggi, 120 x 120 x 208 (cm3), kapasitas maksimal 80 (kg/10jam), bahan bakar arang kayu, dan waktu pengeringan 10 (jam). Rerata capaian suhu pengeringan tertinggi dicapai pada pengeringan cerobong dengan kapasitas 50 (kg/10jam) sebesar 62,3 0C, dengan sebaran suhu antara 62,95 0C-65,45 0C, kebutuhan kalor tertinggi dicapai pada pengeringan cerobong kapasitas 80 (kg) sebesar 14.087,1 (kJ) dengan efisiensi 36,753%, kadar air 12,195 %, kebutuhan udara pengering 16,26397 (kg/jam). Rerata kekuatan tarik terbesar dicapai pada pengeringan cerobong kapasitas 50 (kg) sebesar 23,537 (N/mm2), sedang kekuatan tarik hasil penjemuran hanya sebesar 15,681 (N/mm2), warna paling mendekati alami (kehijauan) terdapat pada hasil proses pengeringan cerobong kapasitas 50 (kg) yaitu L 36,39; sedang warna hasil penjemuran L 51,89. Secara finansial, dengan analisis incremental BCR didapat angka 1,015, analisis NPV Rp. 2.569.148,31, IRR 39 %, dan BEP dicapai setelah alat memproduksi eceng gondok kering 962,1 (kg), atau telah menghasilkan Rp. 5.291.288,30, sehingga pemakaian alat pengering mekanis untuk pengeringan eceng gondok sangat menguntungkan.